THE BUSINESS DEVELOPMENT OF PONDOK SIDOGIRI PESANTREN PASURUAN - Rizal Bagus Pambudi; Achsania Hendratmi (Universitas Airlangga, 2020)
The purpose of this study is to find out the business development process which is conducted by Kopontren Sidogiri in creating Basmalah stores that spread across Indonesia with sharia-based businesses. This study uses a qualitative method by using a descriptive case study method. The object of this study is the Basmalah store. Data were collected using semi-structured interviews on three informants, consisting of the Head of the Marketing Division, the Head of the Operational Division, and the Head of the Area Manager Division. Based on the results of the study, it indicates that the business development carried out by Kopontren Sidogiri is mutually sustainable between one business and another. Kopontren Sidogiri, which is known as a sharia-based cooperative, succeeds in creating three companies, namely PT. Sidogiri Mitra Utama which supervises the Basmalah store, PT. Sidogiri Mandiri Utama which owns Santri AMDK products, and PT. Sidogiri Pandu Utama which manages human resources using the Sidogiri Excel Center (SEC) program or better known as the Sidogiri corporation. The business strength of Sidogiri corporation lies in the relationship created between Alumni of Islamic boarding school and students of Sidogiri so that they can quickly develop their markets, regions and business products. The contract used in opening new branches comes under ijarah, mudharabah, and musyarakah. In every new branch opening of Basmalah store, they conduct recitations that invite community leaders to introduce Basmalah store.Keywords: Business Development, Kopontren Sidogiri, Islamic Boarding School Business, Sharia Business.REFFERENCEAzwar, Adiwarman Karim. (2012). Sejarah pemikiran ekonomi Islam edisi ketiga. Jakarta: PT RajaGrafindo Persada.Badan Pusat Statistik Surabaya. (2014). Jumlah koperasi aktif menurut provinsi, 2006-2016. (https://www.bps.go.id/statictable/2014/01/15/1314/jumlah-koperasi-aktif-menurut-provinsi-2006-2016.html Diakses 18 Juli 2018)Bungin, Burhan. (2007). Penelitian kualitatif edisi kedua. Jakarta: Prenada Media Group.Bungin, Burhan. (2007). Penelitian kualitatif. komunikasi, ekonomi, kebijakan publik dan ilmu sosial lainnya. Jakarta: Putra GrafikaChusmeru, Masrukin, dan Sri Pangestuti. (2017). Koperasi pondok pesantren sebagai pemberdayaan ekonomi santri. Jurnal Universitas Jenderal Soedirman, 7(1), 17-18.Departemen Agama RI. (2006). Al-Quran dan terjemahnya. Bandung: CV Penerbit Diponegoro.Hamidi. Yusuf. (2008). Metode penelitian kualitatif. Malang: Universitas Muhammadiyah Malang Press.Hendratmi, Achsania. (2016). Penggalian dan penemuan model bisnis Islami. Surabaya: Universitas Airlangga.Huda, Nurul dan Mohamad Heykal. (2010). Lembaga keuangan Islam tinjauan teoritis dan praktis. Jakarta: Prenada Media Group.Idri. (2015). Hadist ekonomi dalam perspektif hadis nabi. Jakarta: Prenada Media Group.J, Lexy Moleong. (2017). Metodologi penelitian kualitatif. Bandung: PT Remaja Rosdakarya.K, Yin Robert. (2015). Studi kasus desain & metode. Jakarta: PT RajaGrafindo Persada.Kementrian Koperasi dan Usaha Kecil dan Menengah Republik Indonesia. (2015). (http://www.depkop.go.id/uploads/tx_rtgfiles/1F_Koperasi_Desember_2015.pdf Diakses 13 Agustus 2018)Masngudi, H. (1990). Penelitian tentang sejarah perkemangan koperasi di Indonesia. Jakarta: Badan Penelitian Pengembangan Koperasi Departemen Koperasi.Moleong. Lexy J. (2009). Metode penelitian kualitatif. Bandung: PT. Remaja Rosdakarya Muhammad, bin Abdullah bin Adurahman bin Ishaq Al-Sheikh. (2003). Tafsir Ibnu Katsir. Bogor: Pustaka Imam asy-Syafi’i.Noor, Juliansyah. (2011). Metodologi penelitian skripsi, tesis, disertasi, dan karya ilmiah. Jakarta: Kencana Pernada Media Group. Norvadewi, (2015). Bisnis dalam perspektif Islam. Al-Tijary, 1(1), 33-46.Nridiani, Nina. (2014). Teknik sampling Snowball dalam penelitian lapangan. ComTech, 5(2), 1110-1118.Puji, Rahayu Suci. (2009). Peningkatan kinerja melalui orientasi kewirausahaan, kemampuan manajemen, dan strategi bisnis (studi pada industri kecil menengah bordir di Jawa Timur). Malang: Universitas Widyagama. S, Juhaya Pradja. (2012). Ekonomi syariah. Bandung: Pustaka setiaSolihin, Ismail. (2012). Manajemen strategik. Bandung: Erlangga.Sopandi, Encep. (2017). Strategy of business development bamboo craft (a study in pasirjambu village pasirjambu district Bandung regency). Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, 2(1). https://doi.org/10.24198/adbispreneur.v2i1.12876Sugiyono. (2009). Metode penelitian Kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta.Yin, Robert K. (2015). Studi kasus design & metode. Jakarta: Raja Grafindo Persada.